Identifying The Level of Flexibilty, Agility and Speed Among Track and Field Athletes with Disabilities - Abdullah, Nagoor Meera; Ismail, Wan Hadhilah Wan; Harun, Rohani; Parnabas, Vincent; Nazarudin, Mohamad Nizam; Fauzee, Mohd Soffian Omar (Media Ilmu Keolahragaan Indonesia, 2013)
Abstract In order to become a successful track and fieldÂ athlete, an athlete must develop skills in flexibility, agilityÂ and speed. However, to date, all the research regardingÂ flexibility, agility and speed have concentrated on normalÂ athletes. The present study extends this line of researchÂ to disabled track and field athletes in Malaysia. The aimsÂ of the present study were to achieve the set a benchmarkÂ for measuring level of flexibility, speed and agility amongÂ track and field athletes with disabilities; and to examineÂ the influence of participation in either track or field eventsÂ on the development of flexibility, agility and speed.Thirty-eight (n=38) track and field athletes with disabilitiesÂ comprising of 27 males and 11 females participated inÂ the study. Each participant completed six tests made upÂ of sit and reach test, lateral change of direction test, handÂ grip strength test; back leg dynamometer test and sit-upÂ test. A descriptive analysis was used to assess differencesÂ in performance between track and field athletes withÂ disabilities on the six tests. It was observed that trackÂ athletes with disabilities were superior on agility, speedÂ and agility than field athletes with disabilities. All the dataÂ were analysed using SPSS and presented as mean of (Â±Â SEM). The mean value height and weight for male 168.35Â Â± 1.46m and 66.73 Â± 3.28kg. Meanwhile, the mean valueÂ height and weight for femaleâs 153.82 Â± 2.10m and 45.08Â Â± 1.94kg. For male Body Mass Index (BMI), the mean wasÂ 23.33 Â± 4.5 kg.m2 and 19.09 Â± 1.6 kg.m2 for females. WhenÂ divided according to gender category, the mean backÂ grip test for male subjects was 92.06 Â± 44.2 kg and 48.45Â Â± 17.2 kg for females. Sit-ups test revealed that the meanÂ performance for male was 35.52 Â± 9.8 and 28.36 Â± 8.14 forÂ the female athletes. Besides that in the sit and reach test,Â the mean for male athletes was 30.78 Â± 12.2 cm and 23.18Â Â± 12.40 cm for females athletes. In the hand grip test, maleÂ subjects mean was 70.51 Â± 30.5 kg and 45.47 Â± 15.91 kg for females. The mean value for lateral change of directionÂ test for male athletes was 13.66 Â± 3.7 and 15.78 Â± 2.9 forÂ the female athletes. The field athletes were, however,Â superior on flexibility, back grip test and hand-grip testÂ than track disabled athletes. The results showed the threeÂ measures of flexibility, agility and speed were appropriateÂ for determining the physical fitness level of track and field Â *Faculty of Sports Science and Recreation, UniversitiÂ Teknologi Mara, Malaysia,Â SMK Syed Mashor, Batang kali, Selangor, MalaysiaÂ Faculty of Health Sciences, Puncak Alam Campus,Â Universiti Teknologi Mara, Malaysia,Â School of Education & Social Development, UniversitiÂ Malaysia Sabah, MalaysiaÂ UUM College of Arts and Sciences, Universiti UtaraÂ Malaysia, MalaysiaÂ athletes with disabilities.